Frost‐driven lower treelines in Angola and their implications for tropical forest–grassland mosaics. (25th October 2021) - Finckh, Manfred; Wendefeuer, Janika; Meller, Paulina
Abstract: Questions: Forest–grassland boundaries in the tropics are primarily interpreted as driven by fire and herbivory. So far, frost has received little attention as driver of tropical vegetation boundaries. Here, we study mid‐altitudes in south‐central Africa and ask the following questions: (a) is there a lower treeline between grasslands and forests on the Angolan Plateau; (b) if so, do topoclimatic differences play a role in it; and (c) what do our results imply for tropical highlands globally? Location: The Angolan Plateau (10°–16°S and 13°–21° E). Methods: We mapped vegetation by applying a supervised support vector machine‐based classification on a Landsat satellite image. We used a 1, 000‐m spaced point grid to extract the mean vertical distribution of the vegetation units from a digital elevation model. The topographic position of each point was calculated using a channel network approach. Microclimatic data were collected across topographic gradients at two sites along the Plateau. Analyses focussed on the number of nights where temperature dropped below 0℃, median and minimum temperatures, and diurnal temperature ranges. Results: Lower treelines separate Miombo forests from geoxyle grasslands in all major valley systems. Treelines are located 150–200 m below the headwater divides. Nocturnal outgoing net long‐wave radiation and resulting cold‐air pooling cause frequent frosts in the valleys during the dry season. Topography controls frost patterns, with minima of down to −7.5℃ and diurnal temperature amplitudes up to 40℃. Conclusions: The results show that vegetation patterns in central Angola are shaped by frost. The processes causing frost depend on air humidity. Drier atmosphere and lower global temperatures indicate a longer frost season, lower minima and frost extending to lower elevations and latitudes for the Pleistocene. Pleistocene forest fragmentations and the rise of endemism‐rich grasslands in comparable tropical highlands worldwide may be explained by crossing thermic thresholds via increasing seasonal aridity. Abstract : We describe widespread frost‐driven lower treelines in the Angolan tropics and analyse the topo‐climatic mechanisms causing them. Nocturnal dry‐season frosts occur frequently in mid‐altitudes, caused by outgoing net long‐wave radiation. Our findings challenge the prevailing opinion that frost does not play a major role for tropical forest–grassland boundaries. The results have biogeographical implications for biodiverse tropical grasslands worldwide.